Penerapan system pakar pada aplikasi bengkel online berbasis android untuk meningkatkan pelayanan bengkel - Syafrial Syafrial; Fauzi Fauzi (Sekolah Tinggi Ilmu Komputer Binaniaga, 2019)
Motorized vehicles are the transportation media needed today because moving motorized vehicles make time and energy efficiency. Motorbikes are an ideal transportation medium for traversing increasingly crowded cities. Along with the increasing number of vehicles caused by the community's need for transportation, this means that it is directly proportional to the community's need for vehicle maintenance services such as garage services. At present, the workshop is required to have a different mindset and operational concepts. Excellent service quality for the survival of the company. Good service quality, will satisfy and then make customers become loyal to continue to use these services. Therefore, to get better services, interactive media are needed to increase the level of customer satisfaction. The composer uses the certainty factor system method in the android-based online workshop application so that it can help damage anything discussed on the vehicle and provides solutions obtained from the android-based online workshop application service with the optimal level of customer satisfaction so that it will be able to create loyalty for customers of transportation vehicle users.